Virus-like particles in poultry disease: an approach to effective and safe vaccination - Raji, Abdullahi Abdullahi; Dastjerdi, Paniz Zarghami; Omar, Abdul Rahman (Frontiers Media SA, 2024)
The poultry industry, a cornerstone of global food security, faces dynamic challenges exacerbated by viral diseases. This review traces the trajectory of poultry vaccination, evolving from traditional methods to the forefront of innovation Virus-Like Particle (VLP) vaccines. Vaccination has been pivotal in disease control, but traditional vaccines exhibit some limitations. This review examines the emergence of VLPs as a game-changer in poultry vaccination. VLPs, mimicking viruses without replication, offer a safer, targeted alternative with enhanced immunogenicity. The narrative encompasses VLP design principles, production methods, immunogenicity, and efficacy against major poultry viruses. Challenges and prospects are explored, presenting VLP vaccines as a transformative technique in poultry disease control. Understanding their potential empowers industry stakeholders to navigate poultry health management with precision, promising improved welfare, reduced economic losses, and heightened food safety.